Un archipel des solitudes – perspective à vol d’oiseau – - BANU, Georges (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
An Archipelago of Loneliness – an aerial view. This paper traces a map and a brief history of the presence of Romanian theatre outside the borders of Romania. It is shown here that Romanian theatre artists (actors, stage directors, stage designers) left Romania for many different reasons: a need for affirmation and of international celebrity, political and cultural persecutions etc. The emphasis is put here on the communist period, when the censorship imposed by political power determined many people to exile themselves: Silviu Purcărete, Lucian Pintilie, Andrei Şerban, Liviu Ciulei, as well as the author of this text and many others. What one can see is that Romanian theatre artists worked individually, without building complex networks, even if they sometimes collaborated: that’s the archipelago of loneliness the title mentions. That doesn’t mean they hadn’t any influence on the theatrical life in the countries where they lived: they had a great impact, mainly through the theatre schools they founded.